2022
DOI: 10.1115/1.4054628
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom-Shaped Micropillar With a Maximum Pull-Off Force

Abstract: The bioinspired structure of the mushroom-shaped micropillar has been considered a blueprint of functionalized adhesives due to its prominent dry adhesive performance. Among the design strategies, the geometrical parameters of the stalk and tip are of significance for improving their adhesion performance. In this study, mushroom-shaped micropillars in different diameters of the stalk and tip are fabricated by a new fabrication approach, and the adhesion measurements are performed to study the influences of loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Recently, a novel approach has been proposed for the fabrication of mushroom-shaped adhesives by integrating demolding and laser cutting techniques, as depicted in figure 3(h) [95]. Initially, a thin film with densely arranged micropillar structures is obtained on a negative mold.…”
Section: Fabrication Methods Of Bioinspired Dry Adhesivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a novel approach has been proposed for the fabrication of mushroom-shaped adhesives by integrating demolding and laser cutting techniques, as depicted in figure 3(h) [95]. Initially, a thin film with densely arranged micropillar structures is obtained on a negative mold.…”
Section: Fabrication Methods Of Bioinspired Dry Adhesivesmentioning
confidence: 99%
“…Zhao et al investigated the impact of tip diameter on the failure behavior of adhesion interfaces [95]. Experimental observations revealed that when the tip diameter was small, the failure occurred in the form of edge crack failure.…”
Section: Adhesion Of Bioinspired Dry Adhesivesmentioning
confidence: 99%
“…Switchable adhesives based on structural designs that can offer a wide range of strong to weak adhesion are more attractive for transfer printing. One of the most famous studies is the switchable adhesive inspired by the gecko foot with a fibrillar surface assisted by lateral movement or retraction angle. The other important example of switchable adhesive based on structural designs is the surface topography controllable adhesives by external stimuli (e.g., magnetic field, heating, and pneumatic pressure). In addition to the strategy of structural designs, smart materials (e.g., hydrogel, shape memory polymer (SMP), and liquid metal) with stimuli reactive functions that can complement those on structure designs have been introduced to develop switchable adhesives for transfer printing. The most appealing demonstrations are from the SMPs, which hold great potential for the next-generation functional surfaces due to their unique property of recovering from temporary shapes to the original shape upon external stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…( D ) Adhesion switchability versus adhesion strength of the SMP compared to typical elastomers. The blue spheres represent the adhesion switchability of SMP adhesives, and orange squares represent the adhesion switchability of elastomeric adhesives reported in the literature ( 28 , 34 37 , 70 , 71 , 79 102 ). More details on the data collected from the literature can be found in SI Appendix , section S2 .…”
mentioning
confidence: 99%